Methods and efficacy of processing testicular sperm samples in obstructive and non-obstructive azoospermia: a systematic review - Terrence C. Tsou; Shagnik Ray; Mahir Maruf; Taylor P. Kohn; Mohammad H. Zaman; Michael F. Ayenew; Arvin K. George; Amin S. Herati (Journal of Men's Health)
Intracytoplasmic sperm injection (ICSI) is a cornerstone in managing male infertility, especially in obstructive azoospermia (OA) and non-obstructive azoospermia (NOA), necessitating sperm retrieval via testicular sperm extraction (TESE) or microdissection TESE (mTESE). However, the varied post-sperm extraction processing methods pose uncertainty regarding optimal approaches. To address this, a systematic review following preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) guidelines was conducted, identifying 16 relevant studies. These studies exhibited significant heterogeneity in methodologies and outcomes, with mechanical preparation and enzymatic digestion being the primary techniques investigated. Mechanical methods, including shredding, mincing, vortexing and crushing, yielded varying sperm counts per 100 mg of tissue, with mincing showing promise in NOA cases. Enzymatic digestion, particularly with collagenase type IV, also showed effectiveness, though inconsistently. Additionally, techniques such as microfluidics and magnetic levitation showed potential for improving sperm retrieval efficiency. However, the lack of standardization in outcomes and reporting impedes the establishment of best practice protocols. While collagenase type IV with elastase seemed promising for OA samples and microfluidics for NOA cases, further studies with standardized methodologies and outcomes are necessary. Assessment of DNA damage and comparisons of ICSI success rates between processing methods are crucial for informed clinical practice. In conclusion, optimizing sperm quantity and quality for ICSI necessitates standardized methodologies and outcomes, with microfluidics and collagenase type IV with elastase showing promise pending further validation through well-designed studies.